Optimal choice and beliefs with ex ante savoring and ex post disappointment - Christian Gollier; Alexander Muermann (Goethe University Frankfurt, Center for Financial Studies (CFS), 2006)
We propose a new decision criterion under risk in which people extract both utility from anticipatory feelings ex ante and disutility from disappointment ex post. The decision maker chooses his degree of optimism, given that more optimism raises both the utility of ex ante feelings and the risk of disappointment ex post. We characterize the optimal beliefs and the preferences under risk generated by this mental process and apply this criterion to a simple portfolio choice/insurance problem. We show that these preferences are consistent with the preference reversal in the Allais' paradoxes and predict that the decision maker takes on less risk compared to an expected utility maximizer. This speaks to the equity premium puzzle and to the preference for low deductibles in insurance contracts. Keywords: endogenous beliefs, anticipatory feeling, disappointment, optimism, decision under risk, portfolio allocation.
urn:nbn:de:hebis:30-38022
Keywords: D81; G11; 330; Endogenous Beliefs; Anticipatory Feeling; Disappointment; Optimism; Decision Under Risk; Portfolio Allocation; Anlageverhalten; Entscheidung bei Risiko; Portfolio-Management; Risikopräferenz; Erwartungsnutzen; Theorie